Determinant Motivation and Path Career: Analysis Competence, Job Satisfaction and Leadership - Supardi Supardi (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2023)
The purpose of this study is to provide a result of reviewing twenty-five articles selected based on the variables used as topics. The results of this study have several variables related and the use of one variable with the variables in this study, it's just that it can be used as a reference and continued by other researchers with the same variables as the updated results.